Collaborating Against Child Abuse Exploring the Nordic Barnahus Model - Johansson, Susanna; Stefansen, Kari; Bakketeig, Elisiv; Kaldal, Anna (Springer Nature, 2017)
Scandinavia; child protection; multi-agency working; criminology; policy